Students' Experiences toward Flipped Classroom in Muslim Boarding House Setting - Purnamasari, Mega; Nugraheni, Dyah Ayu (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2023)
This qualitative interview study (Creswell, 2014)aimed at students experience toward flipped classroom in Muslim boarding house setting. Drawing on data collected from semi-structured interviews with 4 participants enrolled in practicing the flipped classroom method at one of private vocational school in the eastern of java, Indonesia, the result of the thematic analysis (Braun & Clarke, 2006) showcased that positively influences the participants felt comfortable, The students perceived flipped classroom as a student-centered, enjoyment, subsequent confidence in the material. Therefore, they recommend this learning model to be incorporated into their classes in the future as a substitute that can increase student interaction and collaboration to learn all the material with available facilities (such as books in the library) and limited use of technology (internet access). Finally, we drew conclusions, limitations, discussing practical implication, and recommendation.